Rancang Bangun Aplikasi Konseling Hiv/Aids Berbasis Web Dengan Penalaran Case Based - Ramayanda, Ramayanda (Jurusan Informatika Universitas Tanjungpura, 2015)
Abstract - HIV / AIDS Counseling is essential in detecting whether someone has been exposed to HIV / AIDS or not. The number of data cases of HIV / AIDS are many and varied, which is obtained either from experience counselors, and case data recorded on the institution of VCT / AIDS, it is possible to apply the reasoning in Case Base Reasoning Counseling HIV / AIDS. The research conducted in this thesis is how to design and build web-based applications with cased based reasoning. This reasoning will be included in an application engineering counseling of HIV / AIDS with a web-based Case Base Reasoning. And with this application is expected to help the socialization and counseling of HIV / AIDS on society. This study resulted in an application counseling HIV / AIDS with a web-based Case Based Reasoning, the method of Simple Matching Coefficient as a method of similarity calculation of binary data. Applications are made for register visitors, leads visitors to the questionnaire, to infer how likely visitors are exposed to HIV / AIDS, by comparing with the existing cases that have been there. Application counseling HIV / AIDS in this study did not determine a person with HIV / AIDS or not, just shows how much the risk of a person is exposed to HIV / AIDS, based on its similarity with the cases that already in the database of cases. Testing results with a user acceptance test shows that this application can be used for the counseling process.